Phase behaviour and physical properties (density and viscosity) of supercritical CO2 + (1-octanol and/or n-alkanes) - Jayeola, Omofolasewa Hillary (Stellenbosch : Stellenbosch University, 2023)
Thesis (MEng)--Stellenbosch University, 2023.